The Legal Position of Underhand Debt Acknowledgment Certificate Legalized by a Notary - Jumades, Achmad; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and identify the legal position of private acknowledgment certificates legalized by a notary and how the notary's responsibility for private acknowledgment certificates is legalized in the event of a dispute between the parties. The approach method used in this study is sociological juridical, the specifications of this research use descriptive analysis, data sources are obtained from primary data and secondary data, namely data obtained from literature and legal materials used, namely primary legal materials, secondary legal materials, tertiary legal materials, which is then analyzed by means of interactive model qualitative analysis.Â Based on the results of data analysis it was concluded that, the legal position of a private acknowledgment of debt legalized by a Notary is the same as an authentic deed, as long as the process of making it fulfills the formal and material requirements and is not denied the truth, this is in accordance with the provisions of Article 1338 paragraph (1) The Civil Code, and the Notary's responsibility for the private acknowledgment of debt which is legalized in the event of a dispute between the parties, the Notary can be asked for information regarding the certainty of the date of the privately owned letter, the authenticity of the signatures of the parties, procedures and mechanisms for legalization, this is in accordance with the provisions of Article 15 paragraph (2) letter (a) of Act No. 2 of 2014 concerning amendments to Act No. 30 of 2004 concerning the Office of a Notary,and Article 1874 of the Civil Code.Keywords: Acknowledgment; Debt; Legalization.